Analysis and numerical approximation of singular boundary value problems with the p-Laplacian in fluid mechanics - Kulikov, G.Yu; Lima, P.M.; Morgado, M.L. (Journal of computational and applied mathematics, 2014)
This paper studies a generalization of the Cahn–Hilliard continuum model for multi-phase fluids where the classical Laplacian has been replaced by a degenerate one (i.e., the so-called p-Laplacian). The solution’s asymptotic behavior is analyzed at two singular points; namely, at the origin and at infinity. An efficient technique for treating such singular boundary value problems is presented, and results of numerical integration are discussed and compared with earlier computed data.